2004
DOI: 10.1509/jmkr.41.2.184.28674
|View full text |Cite
|
Sign up to set email alerts
|

Model of Brand Choice with a No-Purchase Option Calibrated to Scanner-Panel Data

Abstract: In usual practice, researchers specify and estimate brand-choice models from purchase data, ignoring observations in which category incidence does not occur (i.e., no-purchase observations). This practice can be problematic if there are unobservable factors that affect the nopurchase and the brand-choice decisions. When such a correlation exists, it is important to model simultaneously the no-purchase and the brand-choice decisions. The authors propose a model suitable for scanner-panel data in which the no-pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
3
33
0
1
Order By: Relevance
“…Not every single scaling parameter is estimated, but the parameters of their distribution instead. The nested logit approach is predominantly used in the field of transportation research and logistics (Train, 1980;Bhat, 1997;Knapp et al, 2001), but can also be appropriate for marketing issues (Kannan and Wright, 1991;Chintagunta, 1993;Chintagunta and Vilcassim, 1998;Guadagni and Little, 1998;Chib et al, 2004). The nested logit model is the most often used hierarchical model in marketing (Suárez et al, 2004) and can be used for modelling in any situation where subsets of alternatives share unobservable utility components (Ben-Akiva and Lerman, 1985).…”
Section: Discrete Choice Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not every single scaling parameter is estimated, but the parameters of their distribution instead. The nested logit approach is predominantly used in the field of transportation research and logistics (Train, 1980;Bhat, 1997;Knapp et al, 2001), but can also be appropriate for marketing issues (Kannan and Wright, 1991;Chintagunta, 1993;Chintagunta and Vilcassim, 1998;Guadagni and Little, 1998;Chib et al, 2004). The nested logit model is the most often used hierarchical model in marketing (Suárez et al, 2004) and can be used for modelling in any situation where subsets of alternatives share unobservable utility components (Ben-Akiva and Lerman, 1985).…”
Section: Discrete Choice Modelsmentioning
confidence: 99%
“…The nested logit model is the most often used hierarchical model in marketing (Suárez et al, 2004) and can be used for modelling in any situation where subsets of alternatives share unobservable utility components (Ben-Akiva and Lerman, 1985). In the field of marketing the nested logit model is mainly applied in brand choice modelling (Kamakura et al, 1996;Ailawadi and Neslin, 1998;Guadagni and Little, 1998;Sun et al, 2003;Chib et al, 2004), where brands are nested, for example, regarding manufacturer (Anderson and de Palma, 1992); in a purchase incidence decision (Chintagunta, 1993;Chintagunta and Vilcassim, 1998); or regarding brand type (Baltas et al, 1997). One important point to make is that the nested logit model is a combination of standard logit models.…”
Section: Discrete Choice Modelsmentioning
confidence: 99%
“…For example, a segmentation study of customers of Mobil Oil (Forsyth, Gupta, Haldar, Kaul, and Kettle 1999) found that price shoppers spent an average of $700 annually, whereas price-insensitive, heavier users spent as much as $1,200. Similarly, Chib, Seetharaman, and Strijnev (2004) found that the parameters explaining category purchases are correlated with the parameters explaining brand-choice decisions.…”
Section: Introductionmentioning
confidence: 85%
“…The literature describes two approaches to modeling this dependence. One of these approaches is to jointly model brand-choice and category-purchase incidence (Chib et al 2004;Chintagunta 1993;Chiang 1991) or purchase timing (Chintagunta and Prasad 1998), and the other is to jointly model brand-choice and purchase frequencies (Dillon and Gupta 1996). We propose a "conditional likelihood" approach to modeling the dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation